The Transition of Greek Higher Education Institutions to the New Governmental Accounting Framework: An Analysis Based on the Altman Z’’ Score - Ms.Aimilia Zoumi; Dr. Spyridon Goumas (Utilitas Mathematica, 2025)
Aim: This study examines the financial resilience and managerial effectiveness of ten Greek higher education institutions (HEIs) by analyzing changes in their Altman Z’’ Scores from 2017 to 2023, with a particular focus on the impact of Presidential Decree 54/2018, which introduced a new accounting framework. Methodology: In this study the Altman Z’’ Score used as the main tool for measuring financial health of 10 Grrek HEIs to evaluate changes in the scores before and after of the introduction of new accounting framework in public sector. Datas were processed in the statistical program SPSS v. 27. Results: Institutional performance varied widely following the accounting reform. The University of Crete experienced a notable improvement, with its score increasing from 6.625 to 11.708 (p = 0.006), while the Agricultural University of Athens also posted a significant gain, moving from 4.689 to 7.147 (p = 0.024). In contrast, although the Athens University of Economics and Business (5.475 to 7.397, p = 0.070), the University of Ioannina (1.480 to 2.726, p = 0.104), and the University of Thessaly (0.808 to 4.578, p = 0.220) showed some improvement, the changes were not statistically significant. Meanwhile, the University of Patras (8.331 to 7.038, p = 0.616), the University of Macedonia (6.259 to 6.187, p = 0.979), the University of the Aegean (3.553 to 2.091, p = 0.082), the Democritus University of Thrace (1.640 to 1.480, p = 0.601), and Aristotle University of Thessaloniki (1.776 to 2.018, p = 0.654) either saw slight declines or remained largely unchanged, leaving them in what could be considered a "grey area." Conclusion: The results emphasize the critical role of strong internal governance and effective administrative structures in making financial reforms successful. The ability to adopt accrual-based accounting standards like IPSAS depends largely on how well an organization is prepared and how flexibly it can adapt to new demands. Regular monitoring of key financial health indicators is equally important, enablinginstitutions to anticipate challenges early and maintain long-term financial resilience.